THE INFLUENCE OF PRICE, PRODUCT QUALITY, AND SERVICE QUALITY ON COSTUMERS’ SATISFACTION AT TELKOM SEMARANG WIFI CORNER - Fahmi Fahreza; Karnowahadi Karnowahadi; Suwardi Suwardi (Politeknik Negeri Semarang, 2018)
PT Telkomunikasi Indonesia is one of the leading information technology and communication companies in Indonesia. It is always consistent to maintance quality product. The primary purpose of this final project is to analyze the influence of price, product quality, and service quality on costumers’ satisfaction at Telkom Wifi Corner Semarang.The sampling technique used was incidental sampling using Slovin’s formula. The sample was 100 respondents. Method of collecting data were questionnaires and literature study. The statistical analysis used were multiple linier regression method, reliability test, validity test, assumption classic test,coefficient of determination test, F-test, t-test.The result of determination coefficient (R square) showed that 78,1 % costumers’ satisfaction were influenced by price, product quality, and service quality. The rest was explained by other factors not examined in this research. The result of hypothesis testing shows the variables of price, product quality, and service quality simultaneously and partially significant influence on costumers’ satisfaction at Telkom Semarang Wifi Corner.